Sundanese Cultural Values in Paribasa as a Guide to Language Politeness: An Ethnopragmapedagogy Approach - Asep Hidayatullah; Dadang S. Anshori; Andoyo Sastromiharjo (Universitas Syiah Kuala, 2025)
This research aims to identify and analyze the values contained in Sundanese paribasa and explore their application in learning language politeness in pragmatics courses using an ethnopragmappedagogy approach. Through a content analysis method with a qualitative approach, this research succeeded in finding nine indicators of language politeness contained in paribasa, namely: friendly, clear, correct, honest, wise, respectful, sensitive, true to promises, and quality. Friendly indicators emphasize the importance of being open and polite in communication, while clear indicators show the importance of conveying messages that are easy to understand. The correct and honest indicator underlines the importance of honesty and accuracy in every utterance, while the wise indicator emphasizes the ability to consider the impact of each word before conveying it. Respect and sensitivity indicators emphasize that language politeness must pay attention to the feelings and dignity of the interlocutor. Accurate promises underline the importance of consistency in fulfilling commitments that have been made, while quality indicators refer to the importance of speaking with quality that provides benefits and value to the listener. These nine indicators show that Sundanese paribasa can be used as a practical guide in learning language politeness in pragmatics courses through ethnopragmapedagogy. This research concludes that Sundanese paribasa is relevant as teaching material in learning language politeness in pragmatics courses to strengthen ethical awareness in communication